Zinc deficiency and risk of intracerebral hemorrhage: a retrospective cohort study - Chen, I-Wen; Weng, Hsiu-Lan; Ho, Chun-Ning; Liao, Shu-Wei; Lai, Yi-Chen; Wu, Jheng-Yan; Hung, Kuo-Chuan (Frontiers in Nutrition, 2025)
BackgroundIntracerebral hemorrhage (ICH) accounts for 10–20% of all strokes but contributes disproportionately to stroke-related mortality and disability. Zinc, an essential trace element crucial for vascular integrity and antioxidant defense, may influence cerebrovascular health through mechanisms affecting endothelial function and blood–brain barrier stability. However, no large-scale longitudinal study has examined the association between zinc deficiency and ICH risk.MethodsWe conducted a retrospective cohort study using the TriNetX Research Network database, including adults who underwent serum zinc testing between 2010 and 2023. Patients were categorized into zinc deficiency (serum zinc <70 μg/dL) and control groups (70–120 μg/dL). After applying exclusion criteria and 1:1 propensity score matching based on demographics, comorbidities, medications, and laboratory values, we analyzed the association between zinc deficiency and 12-month outcomes, including ICH, mortality, pneumonia, poor blood pressure control, and major adverse cardiac events (MACEs), using Cox proportional hazards regression.ResultsThe final matched cohort included 147,302 patients (73,651 per group). Zinc-deficient patients demonstrated a significantly elevated risk of ICH [hazard ratio (HR): 1.75, 95% confidence interval (CI): 1.35–2.25, p < 0.001], all-cause mortality (HR: 1.90, 95% CI: 1.77–2.03, p < 0.001), pneumonia (HR: 1.50, 95% CI: 1.40–1.60, p < 0.001), poor blood pressure control (HR: 1.26, 95% CI: 1.20–1.32, p < 0.001), and MACEs (HR: 1.12, 95% CI: 1.07–1.18, p < 0.001). A clear dose–response relationship was observed, with severe zinc deficiency (<50 μg/dL) conferring a greater ICH risk (HR: 2.44, 95% CI: 1.50–3.95, p < 0.001). The ICH association remained consistent across patient subgroups, with no significant effect modification. Multivariate analysis confirmed zinc deficiency as an independent ICH predictor (adjusted HR: 1.87, 95% CI: 1.53–2.29, p < 0.001).ConclusionZinc deficiency is a novel, independent, and potentially modifiable risk factor for ICH. The dose-dependent relationship and consistency across patient populations supports biological plausibility. These findings suggest that routine zinc assessment and targeted supplementation in deficient patients may offer new opportunities for ICH prevention, warranting prospective intervention trials to establish causality and optimal therapeutic strategies.